2017
DOI: 10.3889/oamjms.2017.020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Spectrum of Cerebral Palsy and Associated Disability in South Egypt: A Local Survey Study

Abstract: BACKGROUND:Cerebral palsy is the most common cause of motor disability in children with a prevalence of 2-10/1,000 live births in the developing areas.AIM:The epidemiology, clinical picture, and associated comorbidities in CP have been extensively studied in high-resource countries, but in low-resource areas, including Africa, those studies are still lacking.METHODS:Cerebral palsy cases were prospectively recruited from every physiotherapy centre in Bani-Mazar city, Egypt, in a cross-sectional study from May 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 17 publications
(24 reference statements)
2
21
0
Order By: Relevance
“…which is high compared to previously obtained values in this environment and other parts of some developing countries. [11][12][13] The high rate of patients with CP due to birth asphyxia in this study is due to poor obstetrics care occasioned by increasing number of deliveries conducted at home, churches and TBAs where they are unsupervised or attended by untrained midwives.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…which is high compared to previously obtained values in this environment and other parts of some developing countries. [11][12][13] The high rate of patients with CP due to birth asphyxia in this study is due to poor obstetrics care occasioned by increasing number of deliveries conducted at home, churches and TBAs where they are unsupervised or attended by untrained midwives.…”
Section: Discussionmentioning
confidence: 94%
“…Central nervous system infection (meningitis and viral encephalitis) accounted for about a third of the case of CP in this study, a frequency comparable to that previously reported in this environment 4 and other parts of Nigeria and the developing countries in contrast CNS infection contributes a negligible percentage to CP in developed countries. [11][12][13] Congenital malformations of the brain and vascular abnormalities such as cerebral artery occlusion are important causes of cerebral palsy in developed countries, these however, are uncommon aetiologies in developing countries. [10][11][12]14,15 This probably may be related to the unavailability of facilities in some centers of the developing countries where these studies were carried out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our cohort, we found few children with mild impairments (GMFCS level I-II, which was prevalent particularly among the older children in the Ugandan cohort. The high proportion of children with severe impairments are more in par with other clinical cohorts from Uganda, Egypt 4,5,13,14,15 , North India 16 . Many of the children suffered from seizures (61%), and had probably been identified when seeking to get anti-convulsing drugs.…”
Section: Comparison With Other Clinical and Population Based Cohortsmentioning
confidence: 98%
“…1 One reason for this omission, is probably the lack of robust population based studies in Africa and other LMIC. Until recently there were only studies on clinical samples suggesting a wide range of prevalence estimates from 2-10 cases per 1000 children [2][3][4][5] . During recent years, a couple of rigorous population based studies have been published from Uganda 6 and Bangladesh 7 revealing large discrepancies compared with prevalence data from HIC 8 .…”
Section: Introductionmentioning
confidence: 99%